O direito humano à água face à realidade do saneamento básico no Brasil - Parreira, Lucas Silverio (2023)
The present dissertation aims to investigate the human right to water in the context of Brazilian basic sanitation, through studies of public policies developed to provide access to basic sanitation and how its inefficiency can lead to various rights violations, as well as harmful consequences for society and the State. On another note, the intention was to address how public policies related to basic sanitation impact other rights and guarantees already established domestically and internationally, as an expression of human rights. To do so, the relevant regulations were considered, especially the National Basic Sanitation Policy Law - Law 11.445/2007 - with the changes introduced by what is conventionally referred to as the "New Sanitation Framework," given by Federal Law 14.026/2020, as well as its regulatory decrees (Decree 11.466/2023 and Decree 11.467/2023). The dissertation initially deals with establishing a dialogue between human rights and access to basic sanitation operations, in addition to the economic aspect to be considered in basic sanitation operations in the Brazilian state, especially in the state of Goiás. Therefore, based on the results obtained, it was observed that the Regulatory Framework for Basic Sanitation, updated by Federal Law No. 14.026/2020, has as its main objective the goal of providing 99% of the population with drinking water and 90% with sewage collection and treatment by 2033. However, this regulation has opened up real possibilities for the provision of these services by the private sector, even to achieve the goals of the 2030 Agenda. The universalization of basic sanitation operations, especially concerning access to clean and safe water, must be redirected to ensure access to water and basic sanitation services, regardless of the subjective conditions of the users, by consolidating basic sanitation as a fundamental human right, with the clear and precise notation that the underprivileged public should be served regardless of whether the service is provided by the public or private sector, as it is an essential public service.